Genetic transformation in sarpagandha(Rauvolfia serpentina(L.) Benth.) for enhancement of secondary metabolite production - Thangasuja S (Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, 2010)
The present study entitled “Genetic transformation in sarpagandha (Rauvolfia serpentina (L.) Benth.) for enhancement of secondary metabolite production” was carried out at the Centre for Plant Biotechnology and Molecular Biology of the College of Horticulture, Vellanikkara. The objective of the study is to genetically transform Rauvolfia serpentina (L.) Benth. using Agrobacterium rhizogenes by inducing hairy roots so as to enhance the secondary metabolite production. A viable protocol for in vitro propagation of Rauvolfia serpentina was developed. Shoot tip and nodal segment explants from net house grown plants were used for the study. MS media supplemented with BA 1 mg l-1and NAA 0.1 mg l-1 gave maximum regeneration response and also induced multiple shoots (4 shoots/explant) from shoot tip and nodal segment explants. The shoots obtained were best rooted on half strength MS medium supplemented with IBA 0.2 mg l-1and NAA 0.2 mg l-1. The in vitro rooted plantlets were successfully hardened and planted out with 95 per cent survival. Genetic transformation for induction of hairy roots in R. serpentina was attempted with six strains of Agrobacterium rhizogenes, namely ATCC 15834, ATCC 11325, TR 7, A4, TR 107 and MTCC 532. Cefotaxime (500 mg l-1) was found effective for elimination of A. rhizogenes strains from the explant tissues. Different explants such as leaf segments, shoot tips and nodal segments were used for the genetic transformation. The influence of various parameters like co-culture period, acetosyringone treatment and etiolation of shoot tip explant on transformation were studied but none of the treatments showed positive response on induction of hairy roots in R. serpentina. Co-cultivation of shoot tip explant with TR107 strain for two days showed root induction, but the induced roots failed to further proliferate on MS basal medium. Virulence of the different strains and viability of the methodology were checked by inducing hairy roots in Nicotiana tabacum. Among the various explants used for transformation in N. tabacum, leaf segments showed a greater percentage of transformation followed by nodal segment and shoot tip explant. Suspension method of inoculation showed higher percentage of transformation with leaf as explant in ATCC 15834, ATCC 11325 and TR7 strain whereas direct inoculation method showed higher percentage of transformation with leaf as explant in A4, TR 107 and MTCC 532 strain. Among the six strains used for transformation, ATCC 15834 showed the highest frequency of transformation followed by TR7, while TR107 and MTCC 532 failed to infect the explants. The hairy roots induced showed high degree of lateral branching, negative geotropism, fast growth rate and were able to grow in the absence of growth regulators. Opine analysis confirmed the transformation in ATCC 15834, TR7 and A4 hairy root cultures of N. tabacum. Molecular detection through PCR further confirmed the integration of T-DNA from the soil bacteria into hairy root genomes. TR107 induced roots of R serpentina elicited a negative result in PCR amplification as well as opine analysis. Growth rate of hairy roots in liquid culture was faster than in solid media. Half MS with 3.0 per cent sucrose was found to be superior for promoting hairy root growth followed by MS with 3.0 per cent sucrose and B5 with 3.0 per cent sucrose. ATCC 15834 induced hairy roots, showed faster growth producing more biomass as compared to other strains and control. HPLC technique was used for the quantitative analysis of nicotine with the help of class LC10 software (Shimadzu, Japan). Analysis of roots of field grown and in vitro plants as well as hairy root cultures showed that field grown roots had the highest nicotine content followed by hairy roots and attempts were made to enhance the secondary metabolite in hairy root cultures. Enhancement of secondary metabolite production was studied using techniques such as addition of osmoregulants, elicitation and precursor feeding. Addition of 1 per cent sorbitol increased the biomass along with an increase in nicotine content by 2 fold and with further increase in the concentration, the growth rate as well as the nicotine content decreased. Polyethylene glycol at 5 per cent increased the nicotine concentration but there was no increase in biomass production. Yeast Extract at 2 and 5 per cent augmented the nicotine yield but failed to increase the biomass. Addition of the precursor, L-arginine at 50 ppm increased the biomass production along with an increase in nicotine content by 2.6 fold, and with further increase in L- arginine concentration, the nicotine yield dropped down.